Menaik taraf Pasar Taiping, Perak / Syahfi Irfan Syahril - Syahril, Syahfi Irfan (Universiti Teknologi MARA UiTM,Perak, 2022)
Conservation is a process involving of maintaining a place for the purpose of maintaining cultural importance with treatment actions and with circumstances including retention, rehabilitation, redevelopment, and adaptation. Conservation plays an important role in cultural restructuring includes preservation in terms of tangible heritage such as buildings and monuments. In this report, it will be explained about methods used in the conservation project and to investigate times for the project to finish.